Job enrichment, knowledge capital and its impact on strategic success: exploratory study at a sample of the Iraqi government and Private Colleges on Baghdad (Journal of Accounting and Financial Studies ( JAFS ), 2017)
The problem of research was the lack of research that dealt with issue of the job design approach that is more suitable for knowledge work, therefore, the research aims to determine the impact of job enrichment,  and knowledge capitalon strategic success, starting from the hypothesis that there significant impact of job enrichment and knowledge capital on strategic success, to achieve this goal the researchers from the theoretical literature and  related studies conclude to the construction of the scheme shows the hypothetical relationship between the variables, which was adopted job enrichment as independent variable while knowledge capital plays two roles, the first as an independent variable and the second as an intermediate variable,while strategic success representing the dependent variables. The sample consisted of (227) Faculty Member in ten colleges in Baghdad. The research found that the adoption of  job enrichment has a significant impact on knowledge capital and strategic success. The research also found that knowledge capital has a significant impact on strategic success. The research concluded that the effect of job enrichment on strategic success is increasing through knowledge capital. Accordingly, the research recommended the necessity of adopting job enrichment as an approach to design the functions of the knowledge capital owners, And to increase its knowledge capital to  achieve its strategic success.